(untitled) (Research, Society and Development, 2021)
Adhesiveness is an important quality indicator for asphalt mixtures of rolling layers in pavements. Frequent consequences of poor adhesion of the binder to aggregate are slippage and disintegration, as well as reduced durability. Thus, it is necessary to evaluate and fully understand this phenomenon. In the present research, different approaches were used in order to analyze the adhesiveness when there is incorporation of textile sludge, a polluting industrial residue also coming from textile laundries located at the Confeste do APL of Agreste Pernambucano, to asphalt matrices. The sludge was added directly to the adherent material in contents of 2.0 and 3.0% in relation to the total mass of the mixture, and these samples were compared, by means of adhesiveness, to the reference, without sludge. The adhesiveness was analyzed qualitatively by conventional adhesion test described by Brazilian standard DNIT ME 078/1994. The aggregate area covered by ligand was calculated by means of digital image processing and the mixture surface interface was analyzed by microscopy petrographic. The results showed that the insertion of sludge in the mixture does not affect the adhesion of the mixture, since the three samples did not present pickling of the film and the area covered by binder was 100%. Petrographic microscopy showed that the mastic film (binder and textile sludge) penetrated even smaller void pores, this result demonstrates that the increase in viscosity did not harm the spreading on the aggregate surface and that asphalt matrices can be a good form of imprisonment of the studied waste.